التوجيه اللغوية القرارات القرٱنية في كتب معاني القرٱن الزجاج والأخفش الأوسط دراسة مقارنة - عزي، سمية (University of Eloued جامعة الوادي, 2024)
تعد كتب معاني القرآن من أهم المصادر التي يُعتمد عليها في دراسة التفسير وعلوم اللغة العربية. فهي تض ثروة علمية غنية وآراء كثيرة ومتنوعة لعلماء أجلاء، كانوا أئمة العلم في عصرهم. من بين هذه الكتب القيمة نجد كتاب معاني القرآن للأخفش الأوسط، وكتابمعاني القرآن وإعرابه للزجاج، حيث قدما إسهامات بارزة في فهم النص القرآني وتفسيره، مما جعل هذه الأعمال مرجعا لا غنى عنه للباحثين والمهتمين بعلوم القرآن واللغة. وقد سعيت من خلال بحثي الموسوم بـــ: ""التوجيه اللغوي للقراءات القرآنية في كتب معاني القرآن (الأخفش الأوسط والزجاج) -دراسة مقارنة-"" إلى الوقوف على أبرز معالم الاتفاق والاختلاف بين منهج كل من الأخفش الأوسط والزجاج في التعامل مع القراءات القرآنية بأنواعها، وتوجيهها اللغوي، مع إبراز أهم ما اعتمداه من أدوات توجيه القراءات، فكان البحث إجابة على الإشكالية التالية: ما مدى التقارب والتباعد بين منهجي (الأخفش الأوسط والزجاج) في التوجيه اللغوي للقراءات القرآنية من خلال كتابيهما (معاني القرآن)؟ وللإجابة على هذه الإشكالية سرت على خطة مكونة من مدخل تطرقت فيه إلى بعض المفاهيم العامة فقمت بتحديد مفهوم القراءات القرآنية وضوابط قبولها وأنواعها وذكر أشهر القراءات القرآنية، ثم تحديد مفهوم توجيه القراءات، نشأته، أنواعه وأهم أدواته. وفي المبحث الأول تناولت التعريف بالأخفش الأوسط والزجاج وكتابيهما ""معاني القرآن""، مع إبراز القيمة العلمية للمؤلفين وكتابيهما. أما المبحث الثاني عرضت فيه لموقف الأخفش الأوسط والزجاج من القراءات القرآنية بأنواعها، وتتبع منهجهما في التوجيه اللغوي للقراءات من خلال ما وظفاه من أدوات التوجيه. وقد توصلت إلى نتائج مهمة من أبرزها: أن كتابي معاني القرآن للأخفش الأوسط والزجاج، هما في الأساس كتب لغوية تركز على عرض الآراء النحوية والصرفية لهذين الإمامين، متخذين من القرآن الكريم مادة أساسية لدراستهما، وقد قاما بتوجيه القراءات القرآنية من خلال شرح الآيات لغويا وبيان أوجهها، مستندين في ذلك إلى أدلة من القرآن والحديث النبوي الشريف، بالإضافة إلى ما جاء في لغات العرب وأشعارهم وغيرها من الأدوات. وقد اتفقا في بعض المواضع، واختلفا في مواضع أخرى، مما يعكس تنوعا في المنهجية بينهما. Books on the meanings of the Qur'an are among the most important resources relied upon for the study of exegesis and Arabic language sciences. They encompass a rich scientific treasure and a multitude of diverse opinions from esteemed scholars who were leading figures in their time. Among these valuable works are ""Ma'ani al-Qur'an"" by al-Akhfash al-Awsat and ""Ma'ani al-Qur'an wa I'rabuh"" by al-Zajjaj. These books made significant contributions to the understanding and interpretation of the Qur'anic text, establishing them as indispensable references for researchers and those interested in Qur'anic studies and language sciences. In our research titled ""Linguistic Guidance of Qur'anic Readings in the Books of Qur'anic Meanings (al-Akhfash al-Awsat and al-Zajjaj) – A Comparative Study,"" we aimed to identify the key areas of agreement and difference between the methodologies of al-Akhfash al-Awsat and al-Zajjaj in handling various Qur'anic readings and their linguistic guidance. This includes highlighting the primary tools they used to interpret these readings. The research addresses the following question: To what extent do the methodologies of al-Akhfash al-Awsat and al-Zajjaj converge or diverge in their linguistic guidance of Qur'anic readings as presented in their respective works, ""Ma'ani al-Qur'an""? To address this issue, we followed a plan consisting of several parts. In the introduction, we discussed some general concepts, including defining Qur'anic readings, their acceptance criteria, and types, as well as mentioning the most well-known Qur'anic readings. We then defined the concept of guiding Qur'anic readings, including its origins, types, and key tools. In the first section, we introduced al-Akhfash al-Awsat and al-Zajjaj and their respective works, ""Ma'ani al-Qur'an,"" highlighting the scholarly value of the authors and their books. In the second section, we examined the positions of al-Akhfash al-Awsat and al-Zajjaj on the various Qur'anic readings and analyzed their methodologies in the linguistic guidance of these readings through the tools they employed. We reached significant conclusions, including that the books ""Ma'ani al-Qur'an"" by al-Akhfash al-Awsat and al-Zajjaj are fundamentally linguistic works focusing on presenting the grammatical and morphological opinions of these two scholars, using the Qur'an as their primary material. They guided Qur'anic readings by linguistically explaining verses and demonstrating their various aspects, relying on evidence from the Qur'an, Hadith, and other sources such as Arabic languages and poetry. They agreed on some points and differed on others, reflecting a diversity in their methodologies."
مذكرة ماستر تخصص لغة ودراسات قرآنية
Keywords: التوجيه اللغوي القراءات القرآنية الأخفش الأوسط الزجاج Linguistic guidance Quranic readings Al-Akhfash Al-Awsat Al-Zajjaj